Aged Translucent Aesthetic Zirconia: Bond Strength Analysis - Gallina, Bernardo Luiz; Busato, Mauro Carlos Agner; Sicoli, Eliseu Augusto; Camilotti, Veridiana; Mendonca, Marcio Jose (European Journal of Dentistry, 2019)
Objective This study evaluates the bond strength of two compositions of aesthetic translucent zirconia (TZ).Materials and Methods For this evaluation, test specimens were prepared from ICE Zirkon TZ and Prettau Anterior zirconia (PAZ) that were stored in distilled water at 37°C for two time periods: T1 (24 h) and T2 (90 days) to simulate aging. Two factors were evaluated for the samples—ceramic and aging time. The samples were subjected to tests of microshear strength and fracture type and were evaluated using scanning electron microscopy.Results The results were analyzed using the D'Agostino test, analysis of variance, and Tukey's test (p < 0.01). Statistically significant differences were observed for ceramic type and aging time.Conclusion The results showed that PAZ provides significantly superior performance to TZ at the two aging times evaluated.
Keywords: bond strength; microshear; zirconia